(untitled) (Dhaka University Journal of Biological Sciences, 2017)
Five fungicides viz., Bavistin DF, Capvit 50 WP, Dithane M-45, Greengel 72 WP and Tilt 250 EC were selected to evaluate in vitro efficacy against Fusarium oxysporum and F. solani at 100, 200, 300, 400 and 500 ppm following poisoned food technique. Bavistin, Capvit and Tilt were found to be most effective inhibitor against the test pathogens isolated from brinjal wilt. Bavistin and Tilt completely inhibited the growth of F. oxysporum and F. solani at all the tested concentrations. Out of five plant extracts, Allium sativum identified as the promising botanical fungicide for testing against wilted plants of brinjal. The result of present study will be helpful in suggesting some effective plant extracts and fungicides for controlling wilting of brinjal. Dhaka Univ. J. Biol. Sci. 26(1): 39-44, 2017 (January)